Finiteness, "Frequenting the World" and Human Formation on Michel de Montaigne - Rosana Silva de Moura (Universidade Federal do Rio Grande do Sul, 2014)
The paper aims to think about the human development from some aspects of the philosophy of Michel de Montaigne offered to us in the classic text Essays. Initially, it introduces an outline of the Renaissance age, the basis of his anthropological perspective, marked by the man's importance in the world. Based on a hermeneutics of Montaigne´s essays, it interprets the idea of finiteness and of frequentation brought by the author as part of foundational elements of his philosophical horizon. The contribution of Michel de Montaigne' philosophy of education points, precisely, to the open and inconclusive (and therefore rich) character of life, of human development and of education.